Faustian Bargain The Soviet-German Partnership and the Origins of the Second World War - Johnson, Ian Ona (Oxford University Press, Incorporated, 2021)
Offers the full story of a fateful alliance between past and future mortal enemies--long preceding the well-known Ribbentrop-Molotov Pact--whose dimensions were kept secret from the outside world and yet which set the stage for World War Two and its outcome.